Kepercayaan Adat Dayak Tomun: Mekanisme Solidaritas Sosial, Kontrol non-formal, dan Adaptasi Budaya di Era Modernisasi - David Iman Tu’o; Yanto Sandy Tjang; Felisitas Yuswanto (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2026)
This study analyzes the role of the indigenous belief system of the Dayak Tomun community as a foundation for social solidarity, a mechanism of non-formal social control, and a strategy of cultural adaptation in the context of modernization. Grounded in Émile Durkheim’s sociology of religion, particularly the concepts of mechanical solidarity and collective consciousness, this research employs a qualitative approach through a phenomenologically oriented literature review. Data were obtained from ethnographic documents, customary law manuscripts, scholarly articles, and official publications. The findings indicate that indigenous rituals, such as Babukung and Bana’i Tamu, function as means of strengthening emotional bonds and reproducing collective values through communal participation and sacred symbols. Customary law and the pamali system operate effectively as mechanisms of non-formal social control derived from supranatural authority, while simultaneously serving as strategies for ecological conservation. Indigenous beliefs also constitute the foundation of collective consciousness through the internalization of values such as mutual cooperation, respect for nature, and veneration of ancestors. Amid modernization, the Dayak Tomun community demonstrates creative adaptation through ritual reinterpretation, flexible application of pamali, and the integration of formal education with indigenous knowledge. This study affirms that the indigenous belief system of the Dayak Tomun functions as a strategic social, cultural, and ecological instrument in sustaining social cohesion, community resilience, and the continuity of collective identity in the face of contemporary social transformation.